Compression and hysteresis responses of multilayer gradient composite lattice sandwich panels. (January 2021) - Li, Shuang; Yang, Jin-Shui; Schmidt, Rüdiger; Wu, Lin-Zhi; Schröder, Kai-Uwe
Abstract: In order to improve the combat effectiveness, stealth and safety of the marine structures, we design and fabricate the multilayer gradient composite lattice sandwich panels (MGCLSPs) to achieve excellent mechanical properties, vibration isolation characteristics and lightweight features of structures in the present study. The ideas of bionic gradients and material mixtures are incorporated in the design to improve the damping and vibration isolation behaviors of the MGCLSPs. The compression and hysteresis responses of the empty and polyurethane foam-filled MGCLSPs are investigated experimentally and numerically. It is found that the MGCLSPs have better energy absorption characteristics than the non-gradient panels, and the MGCLSP specimen D1 which is positive gradient absorbs the most energy. The experimental results also show that the addition of polyurethane foam can enhance the strength and energy absorption characteristics of MGCLSPs. Highlights: Empty and foam-filled multilayer gradient composite lattice sandwich panels are designed and fabricated. Compression and hysteresis tests are conducted to investigate the energy absorption characteristics of the structures. The multilayer gradient panels have better energy absorption characteristics than the non-gradient panels. The addition of polyurethane foam can enhance the strength and energy absorption characteristics of the present structures.